ANALYSIS OF CUSTOMER BANK BRI SYARIAH PREFERENCES OF CIAMIS BRANCH OFFICES ON FUNDING PRODUCT ATTRIBUTES - Dudi Badruzaman (Universitas Islam Negeri Mataram, 2020)
This study analyzes the product attributes of fund collection that are the customer preferences of Bank BRI Syariah Ciamis Branch Office and analyzes the attributes that are most considered by customers in using fund collection products. The basic method of this research is descriptive. The method of analysis of customer preferences is the chi-square analysis and to analyze the attributes that are most considered by customers is the Fishbein multi-attribute analysis. It is known that customer preferences for product attributes of raising funds are a proportion of larger profit-sharing ratios for customers, many ATM network facilities, friendly service, affordable public transport office locations. Product attributes of fund collection that are considered by customers in using BRI Syariah fund collection products at the Ciamis Branch Office are locations with attitude index values ??(Ao).